Progress in the application of novel inflammatory indicators in chronic kidney disease - Gao, Wenrui; Wang, Xiangyu; Zou, Yulin; Wang, Sheng; Dou, Jun; Qian, Senlin (Frontiers in Medicine, 2025)
Chronic kidney disease has become a public health problem endangering the health of all humans because of its high prevalence, high mortality and high medical burden. The chronic micro-inflammatory state is recognized as a significant component of CKD, playing a key role in disease progression. Intervening in chronic inflammation during the disease course can enhance prognosis. Recent studies have demonstrated that novel inflammatory indices, such as the neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and systemic immune-inflammatory index are closely associated with CKD, meanwhile may serve as prognostic monitors of all-cause death and poor renal prognosis for the disease. This article comprehensively reports on the mechanisms of micro-inflammation in CKD, the relationship between inflammatory indicators and CKD, and their impact on prognosis.